2018
DOI: 10.1108/jic-03-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

Academic spinoffs as a value driver for intellectual capital: the case of the University of Pisa

Abstract: Purpose: The purpose of this paper is to discuss academic spinoffs (ASO) as an expression of the value creation of university technology transfer (TT) investments. More recently, scholars have emphasised intellectual capital (IC) importance, also for universities in obtaining competitive advantages and by creating value. Such spinoffs are key to regional development, as a primary aspect of universitiesâ\u80\u99 IC. Design/methodology/approach: The authors tested the aim through a sample of the University of Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 89 publications
(114 reference statements)
1
30
0
7
Order By: Relevance
“…Due to its completeness and granularity, the present research utilizes Ramirez, Tejada, and Manzaneque's operationalization of IC (2016) as the basis for its conceptual framework. Borrowing from prior work (Meritum Project, 2002;Hudson, 1993;Stewart, 1997;Mouritsen et al, 2001), the three authors combine different nuances to produce the following definition of IC, which we complement with a fourth dimension, connectivity between components (Mariani et al, 2018) (Table I). Table I here Low, Samkin, and Li (2015), universities mainly disclose information about HC and SC, and less about RC.…”
Section: Technology Adoption and Intellectual Capital In Universitiesmentioning
confidence: 99%
“…Due to its completeness and granularity, the present research utilizes Ramirez, Tejada, and Manzaneque's operationalization of IC (2016) as the basis for its conceptual framework. Borrowing from prior work (Meritum Project, 2002;Hudson, 1993;Stewart, 1997;Mouritsen et al, 2001), the three authors combine different nuances to produce the following definition of IC, which we complement with a fourth dimension, connectivity between components (Mariani et al, 2018) (Table I). Table I here Low, Samkin, and Li (2015), universities mainly disclose information about HC and SC, and less about RC.…”
Section: Technology Adoption and Intellectual Capital In Universitiesmentioning
confidence: 99%
“…Most importantly, the paper shows how the technology and knowledge developed by universities are transferred to communities, and how the benefits are multiplied rather than directly transferred. Through measurements of value and multipliers, Mariani et al (2018) demonstrate the relationship between investment in innovation and the enterprise value of academic spinoffs, which they use as a proxy for investment output and an expression of IC creation. The paper is innovative because it provides insights into how a university can create value for an economy and help build the IC of the communities in which the spinoffs exist.…”
Section: The Impact Of Higher Education On Entrepreneurial Intention mentioning
confidence: 99%
“…Academic Entrepreneurship is the founding of a firm, academic spin-offs, created to commercialize a patented invention or non-patented expertise (Shane, 2004), and is a widely accepted strategic tool for economic and social growth (Audretsch, 2012;Bolzani, Munari, Rasmussen & Toschi, 2020;Mariani, Carlesi & Scarfò, 2017). Indeed, academic spin-offs have a determinant impact on the area in which they operate, from both an economic and social perspective (Vincett, 2010;Zucker, Darby & Brewer 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, academic spin-offs have a determinant impact on the area in which they operate, from both an economic and social perspective (Vincett, 2010;Zucker, Darby & Brewer 1994). They strengthen the impact of intellectual capital on local economic growth (Mariani et al, 2017). Furthermore, it has been demonstrated that entrepreneurial behaviour positively affects scientists' research performance (Van Looy, Ranga, Callaert, Debackere & Zimmerman, 2004).…”
Section: Introductionmentioning
confidence: 99%